Sistema de costos ABC: una herramienta para el proceso de toma de decisiones para las cooperativas de ahorro y crédito de la ciudad de Barranquilla (2013)
The article describes the problems of traditional cost systems used by credit cooperatives in Barranquilla regarding financial decisions. It suggests the ABC (Activity Based Costing) methodology as an alternative in the decision making process. The research done was quantitative, descriptive and deductive. A causal non-experimental correlational design was used. The cooperatives were selected by simple random probability sampling, and subjected to a Likert-type survey. The results showed that these entities are characterized by the use of traditional cost systems with predetermined historical basis which are difficult to guide a decision making process. It was found that the ABC system achieved an accurate allocation of CIF and an appropriate financial decision making process. It concludes that the implementation of the ABC cost system would identify the necessary costs for the provision of services, providing comprehensive information that will facilitate the conditions for establishing the causes and behavior of the CIF, furthering an adequate decision making processes